A Primer on the Current State-of-the-Science Neoadjuvant and Adjuvant Therapy for Patients with Locally Advanced Rectal Adenocarcinomas. (16th May 2012) - Yorio, Jeffrey T.; Bhadkamkar, Nishin A.; Kee, Bryan K.; Garrett, Christopher R.
Abstract : Patients with rectal cancers, due to the unique location of the tumor, have a recurrence pattern distinct from colon cancers. Advances in adjuvant therapy over the last three decades have played an important role in improving patient outcomes. This article serves to review the clinical studies that lay the basis for our current standard-of-care treatment of patients with locally advanced rectal cancer, as well as touch upon future ongoing experimental clinical trials of adjuvant chemoradiation therapy.